Ruling culture : art police, tomb robbers, and the rise of cultural power in Italy - Greenland, Fiona (Chicago scholarship online, 2021)
Through much of its history, Italy was Europe's heart of the arts, an artistic playground for foreign élites and powers who bought, sold, and sometimes plundered millions of Italian artworks and antiquities. This loss of artifacts looted by other nations once put Italy at an economic and political disadvantage compared with northern European states. Now, more than any other country, Italy asserts control over its cultural heritage through a famously effective art-crime squad that has been the inspiration of novels, movies, and TV shows. With 'Ruling Culture', Fiona Greenland traces how Italy came to wield such extensive legal authority, global power, and cultural influence - from the nineteenth century unification of Italy and the passage of novel heritage laws, to current battles with the international art market